Scalable synthesis of holey graphite nanosheets for supercapacitors with high volumetric capacitance. Issue 2 (13th December 2018) - Wang, Jie; Park, Teahoon; Yi, Jin Woo; Ding, Bing; Henzie, Joel; Chang, Zhi; Dou, Hui; Zhang, Xiaogang; Yamauchi, Yusuke
Abstract : We developed a simple and scalable method to fabricate holey graphite nanosheets (HGNs) using GO as the carbon source and ZnO as an etching agent. Abstract : We prepared a material composed of high-density holey graphite nanosheets (HGNs) that supports a high gravimetric capacitance of 295 F g −1 and a volumetric capacitance of 384 F cm −3 for use as electrodes in supercapacitor devices. This method is a simple and scalable route to obtain large amounts of holey two-dimensional materials with high electrochemical performances.